Abrikosov-like lattices in organic crystals on graphite surface. Issue 1663 (9th April 2014) - Fonseca, Alexandre F.; Lisboa-Filho, Paulo N.
ABSTRACT: The interest for surface patterning presents a fast increasing in the last few years due to several factors ranging from miniaturization trends and sensor design to worries about the absorption of carcinogenic molecules on inhalable particles. Although the existence of a vast literature regarding the self-assembly and patterning of nanoparticles on different types of surfaces, it remains unclear the dynamics and main mechanisms behind the formation and maintenance of two-dimensional symmetric patterns of small molecules on top of surfaces. In this contribution, we report initial results on an investigation on the similarities between the well-known Abrikosov hexagonal lattices in superconductors, and the spontaneous formation of hexagonal patterns of some small polycyclic aromatic hydrocarbons (PAHs) on top of a graphitic surface. In order to attest our results, some experimental results from literature are compared to the obtained results.